Diagnosing the raising issues of integrating multiple applications among government agencies in using mykad technology / Dayana Faziha Alias - Dayana Faziha, Alias (2004)
MyKad is the initiatives of the Malaysian Government in providing the public with added convenience on a single card. Unlike any other card in the world,MyKad incorporates a host of Government and private sector applications in a single card. Moreover, MyKad based on the chips and biometrics smart card technology is also able to accommodate new expansions in the future. This MyKad is cost effective and scalable, with the ability to integrate with existing government legacy.